Eclipse of God : studies in the relation between religion and philosophy - Buber, Martin, 1878-1965 (Princeton University Press, 2016)
Biblical in origin, the expression "eclipse of God" refers to the Jewish concept of hester panim, the act of God concealing his face as a way of punishing his disobedient subjects. Though this idea is deeply troubling for many people, in this book Martin Buber uses the expression hopefully-for a hiding God is also a God who can be found.First published in 1952, Eclipse of God is a collection of nine essays concerning the relationship between religion and philosophy. The book features Buber's critique of the thematically interconnected-yet diverse-perspectives of Soren Kierkegaard, Hermann Cohen, C.G. Jung, Martin Heidegger, and other prominent modern thinkers. Buber deconstructs their philosophical conceptions of God and explains why religion needs philosophy to interpret what is authentic in spiritual encounters. He elucidates the religious implications of the I-Thou, or dialogical relationship, and explains how the exclusive focus on scientific knowledge in the modern world blocks the possibility of a personal relationship with God.Featuring a new introduction by Leora Batnitzky, Eclipse of God offers a glimpse into the mind of one of the modern world's greatest Jewish thinkers.